Evaluation of a Database of the Spanish Wind Energy Resources Derived from a Regional Reanalysis - Jiménez-Garrote, Antonio; Santos-Alamillos, Francisco Javier; Sánchez-Hernández, Guadalupe; López-Cuesta, Miguel; Ruiz-Arias, José Antonio; Pozo-Vázquez, David (MDPI, 2024)
An enhanced database (RetroDB) of the Spanish wind energy resources, derived from a high spatial resolution integration with the WRF model, is proposed and evaluated. RetroDB provides hourly capacity factor (CF) values for the Spanish regions, along the period of 2007–2020, with an unprecedented spatial resolution. RetroDB estimates were benchmarked based on the ERA5 global reanalysis. A comprehensive evaluation study of both RetroDB and ERA5 estimates was conducted using surface and tall mast measurements, along with actual CF values. The extent to which RetroDB and ERA5 reproduced the CF spatial variability, distribution, and ramp distribution were specifically addressed. The results showed no differences between the global and regional reanalysis performance regarding nationally aggregated wind energy estimates. Nevertheless, RetroDB clearly shows a superior performance reproducing the wind speeds’ and CFs’ spatial and temporal distributions. This was found to be related to the higher reliability of RetroDB reproducing the aloft winds in complex topographic areas. Overall, the results clearly indicate that, in areas such as the study region, where the wind resources are mostly associated with topographic enhancements, high spatial resolution regional reanalyses are preferable over relative coarse reanalyses (e.g., ERA5), particularly for wind energy integration studies. RetroDB database is made publicly available.
Keywords: Centrales eólicas - España - Bases de datos; meteorology; resource assessment; wind power; wind power integration; wind resource